(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
The material LiCaAlF\(_6\):Eu (0.1 mol%) in microcrystalline form was prepared through water solution coprecipitation method followed by melting it at around 900 \(^°\)C in a graphite crucible. The ingot was crushed and sieved through standard sieves to obtain powder approximate in the range 100-125 \(μ\)m. The material was annealed at around 200-800 \(^°\)C. The material was characterized by XRD. The materials were irradiated to different doses of \(γ\)-rays using \(^60\)Co radioactive source and thermoluminescence (TL) glow curves were recorded. The powder material was found to be at least 10 times more sensitive than CaSO\(_4\):Dy commercially available TLD pellets. However, as the dosimetry peak is at around 180 \(^°\)C, there is fading around 20%. Considering these facts, the material could be considered as a highly sensitive and suitable TLD phosphor.